Feasibility of neonatal screening for Duchenne muscular dystrophy. Issue 1 (February 1982) - Skinner, R; Emery, A E; Scheuerbrandt, G; Syme, J
Abstract : During the period November 1976 to September 1980, 2703 babies born in one Edinburgh hospital were screened in the neonatal period by estimation of their serum creatine kinase levels for Duchenne muscular dystrophy. Among the 2336 male babies tested, none proved to be affected and only 16 required second specimens to be obtained. Overall the false positive rate in the study was 0.78%. This study confirms that neonatal screening for Duchenne muscular dystrophy is feasible in a British hospital setting and is here most conveniently carried out on the 5th day of life along with routine testing for phenylketonuria.